Diagnostic Errors in Wilms' Tumors: Learning From Our Mistakes - Lucas Garschagen de Carvalho; Thiago Kobayashi; Monica dos Santos Cypriano; Eliana Maria Monteiro Caran; Henrique Manoel Lederman; Maria Teresa de Seixas Alves; Simone de Campos Vieira Abib (Frontiers Media S.A., 2021)
Aim: This study aimed to analyze clinical characteristics and image findings in patients initially diagnosed with renal masses and treated on the Société Internationale d'Oncologie Pédiatrique (SIOP) 2001 protocol for Wilms tumor (WT) that eventually were diagnosed with different pathologies.Methods: We reviewed the preoperative symptoms, laboratory tests, and images of patients who were initially treated for WT and proved to have other diagnoses. Data from these patients were compared to those of the last 10 patients with WT and the last 10 patients with neuroblastoma (NBL) treated at a single institution.Results: From June 2001 to December 2020, we treated 299 patients with NBL and 194 with WT. Five patients treated with preoperative chemotherapy for WT were postoperatively diagnosed with NBL (one patient had bilateral renal masses and one with multifocal xanthogranulomatous pyelonephritis). Three underwent nephrectomy, two biopsies only, and one adrenalectomy due to intraoperative characteristics. Regarding clinical presentation, abdominal mass or swelling was very suggestive of WT (p = 0.011); pain, although very prevalent in the study group (67%), was not statistically significant, as well as intratumoral calcifications on computed tomography (CT) (67%). Urinary catecholamines were elevated in all patients mistreated for WT with the exception of the patient with pyelonephritis in which it was not collected.Conclusion: Some pathologies can be misdiagnosed as WT, especially when they present unspecified symptoms and dubious images. Diagnostic accuracy was 98.1%, which highlights the quality of the multidisciplinary team. Abdominal mass or swelling is highly suggestive of WT, especially in the absence of intratumoral calcifications on CT. If possible, urinary catecholamines should be collected at presentation as they help in the differential diagnosis of NBL.